Los procedimientos en la minería ilegal y los derechos constitucionales. - Abarca Tixe, Sonia Marlene (2023)
The present research is entitled “ILLEGAL MINIG PROCEDURES AND CONSTITUTIONAL RIGHTS", and has originated because there are illegal mining activities in Ecuador. Therefore, the purpose of this investigation is to describe whether or not this illegal mining activity affects the constitutional rights of both nature and people. For compliance, the research was developed in two parts: first by treating the constant theoretical framework in 3 units called: the first, regulations on mining, the second, referring to the sanctioning administrative procedure, and the third on constitutional rights. The methodological design appropriate to a social legal investigation, through the historicallogical research method, legal, legal-doctrinal, legal-analytical and deductive comparison; qualitative research approach; types of bibliographic, field and exploratory research; nonexperimental research design. Additionally, information has been collected thanks to the research instruments, with which it has benn possible to draw conclusions and recommendations according to the problem investigated.